2010
DOI: 10.1007/s00428-010-0967-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased neuroendocrine cells in resected metastases compared to primary colorectal adenocarcinomas

Abstract: Neuroendocrine differentiation has been described in rectal adenocarcinomas receiving neoadjuvant therapy prior to radical surgery, but its clinical relevance is controversial and no data are currently available in colorectal carcinoma metastases as compared to primary tumors. The presence of chromogranin A positive tumor cells was investigated by means of immunohistochemistry on surgical specimens from 54 primary colorectal carcinomas and their corresponding metastases, resected at diagnosis or during tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
3
12
0
Order By: Relevance
“…Neuroendocrine differentiation, defined by immunohistochemical staining with antichromogranin A and antisynaptophysin antibodies, has been described in several types of adenocarcinomas 3. Some authors suggested that neuroendocrine differentiation was useful for distinguishing ITAC from sinonasal metastatic CRA 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine differentiation, defined by immunohistochemical staining with antichromogranin A and antisynaptophysin antibodies, has been described in several types of adenocarcinomas 3. Some authors suggested that neuroendocrine differentiation was useful for distinguishing ITAC from sinonasal metastatic CRA 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, metachronous metastases are rarely biopsied, and nuclear medicine tools cannot help distinguishing between adenocarcinoma and PDNEC because, for example, both components display 18 FDG positron-emitting tomography positivity, and negative somatostatin receptor scintigraphy due to lack of somatostatin receptors expression [83] . The cell type present in tumour emboli on resected primary tumours may be similar to that found in lymph node and distant metastases; thus, its analysis could be an alternative to metastasis biopsy [22] .…”
Section: Management Of Minenmentioning
confidence: 99%
“…Besides, radiotherapy and chemotherapy might favour genomic instability and transdifferentiation towards the PDNEC component, based on observations that the number of neuroendocrine markers-positive cells increased following neo-adjuvant treatments [18,65] . This strongly suggests that the PDNEC component develops during a classic adenoma-adenocarcinoma sequence.…”
Section: Pathogenesis and Molecular Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that the adenocarcinoma changed into NEC subsequent to the initial diagnosis. One previous report has shown that neuroendocrine differentiation is more frequently observed in metastatic cancers compared with primary site tumors (9), whereas other reports have described cases wherein chemotherapy was shown to cause histological conversions (10,11). This phenomenon has also been observed in cases of prostate cancer and NSCLC, but the underlying mechanism is unknown (12).…”
Section: Discussionmentioning
confidence: 99%